Pengembangan Produk Unggulan Olahan Bengkoang Desa Cintamulya, Kecamatan Candipuro, Lampung Selatan - Ramanda, Muhammad Rizky; Syafitri, Yosi (TeknoKreatif: Jurnal Pengabdian kepada Masyarakat, 2024)
Cintamulya is one of the leading villages in South Lampung Regency which is currently launching the "Smart Village" concept. The concept of "Smart Village" is a village that applies appropriate technology to develop potential, improve the economy, and create convenience in all aspects of people's lives. The potential that is being intensified by Cintamulya village is in the field of food, where one of the leading agricultural commodities is bengkoang. It's only recently that bengkoang has experienced an increase in the amount of production so that many unsold bengkoang are even left to rot. So that ITERA Food Technology and the Agropreneur MSME in Cintamulya village took the initiative in developing bengkoang derivative products. Processed products from cavendish bengkoang that are in great pain to be developed and sold are bengkoang starch which can be made into mask powders and syrup glucose.